Review Hipotesa Biaya Politik dan Biaya Kontrak Serta Implikasinya pada Laporan Keuangan dan Pembuatan Standar - Ghofar, Abdul (TEMA, 2003)
This article tries to review theoretically and empirically about two phenomena which conflicting each other, namely disclosure and earning management, and also see its influence at making of financial statement and financial accounting standard. This article wish to indicate that two conflicting phenomena could be explained by the same theory. Theoretically that two phenomena are explainable with two hypothesis, namely contractual and political hypothesis. Empirical verification indicates that hypothesis of Political Cost and the Contractual Cost supported by fact as well as can explain phenomena of disclosure and earning management. Empirical verification conducted by observing the relation between the ownership concentration of share ( as variable of contractual cost) with disclosure level and the relation between ownership concentration with earning management. It is concluded that more diverse the ownership, higher the level of disclosure. In the other hand, more diverse the ownership, bigger the possibility of earning management will occur. This verification gives signal to all Accounting standard maker that compiled standard has to be able to lessen non ethical practice among the financial statement maker. For investors this verification gives a warning that financial statement still be possible to contain the opportunistic behavior offinancial statement maker, although such financial statement already based on proper accounting standard.